Intimate Partner Violence in LGBTQ Lives. - Ristock, Janice L. (Taylor & Francis, 2011)
Queer lives remain at the margins of most academic inquiry into domestic violence. This edited volume seeks to change this discourse by bringing together the most innovative research about intimate partner violence that is specific to the lives of lesbian/ gay/ bisexual/ transgender/Two-Spirit and queer people (LGBTQ).